2013
DOI: 10.1039/c2fo30233k
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal anti-inflammatory activity of red wine extract: unveiling the mechanisms in colonic epithelial cells

Abstract: The development of new therapeutic approaches, combining efficacy and safety against intestinal inflammation, notably inflammatory bowel disease (IBD), has emerged as an important goal due to the significant side effects and the lack of effectiveness of standard current therapies. Recently, several studies described the health-promoting effects of red wine, including anti-inflammatory properties, but the molecular mechanisms underlying its beneficial role remain largely unknown. Red wine is rich in phenolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 78 publications
(83 reference statements)
3
53
0
Order By: Relevance
“…The present data are in accordance with other previous studies reporting the inhibitory activity of anthocyanins on the NF- κ B proinflammatory pathway in Caco-2 cells [10, 31, 32]. Furthermore, in vivo studies demonstrated that feeding pigs with an anthocyanin-rich extract reduces transactivation of NF- κ B in the duodenal mucosa and in turn lowers transcript levels of various NF- κ B target genes involved in the inflammatory process [33].…”
Section: Discussionsupporting
confidence: 93%
“…The present data are in accordance with other previous studies reporting the inhibitory activity of anthocyanins on the NF- κ B proinflammatory pathway in Caco-2 cells [10, 31, 32]. Furthermore, in vivo studies demonstrated that feeding pigs with an anthocyanin-rich extract reduces transactivation of NF- κ B in the duodenal mucosa and in turn lowers transcript levels of various NF- κ B target genes involved in the inflammatory process [33].…”
Section: Discussionsupporting
confidence: 93%
“…Wine extract decreased the degradation of Inhibitor of NF-κB, the synthesis of inducible nitric oxide synthase, COX-2 and IL-8 [65]. Similarly, human colon-derived CCD-18Co myofibroblast cells pre-treated with Port Barrel Reserve red wine polyphenolic extract (LeNoir grapes—Texas) and then treated with LPS showed decreased mRNA of both NF-kB and adhesion molecules, depending on the wine-extract concentration.…”
Section: Effects Of Wine On Intestinal Damagementioning
confidence: 93%
“…Phenolic compounds are secondary plant metabolites accumulated in grapes, occurring in all grape parts including skin and seeds and being extracted to wines during the winemaking process. It is well known that phenolic compounds from wines exhibit positive influence on health status acting as exogenous natural antioxidants with long-time proved efficiency in inhibiting the lipoperoxidation (Barreiros et al 2006), as anti-inflammatory agents (Nunes et al 2013) or as carcinopreventive agent compounds (Clifford et al 1996).…”
Section: Introductionmentioning
confidence: 99%